2009
DOI: 10.1007/s00125-009-1418-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancies in patients with diabetes treated with human insulin or insulin analogues: a cohort study

Abstract: Aims/hypothesis The aim of this cohort study was to investigate the risk of malignant neoplasms and mortality in patients with diabetes treated either with human insulin or with one of three insulin analogues. Methods Data were provided by the largest German statutory health insurance fund (time-frame:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
486
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 548 publications
(508 citation statements)
references
References 22 publications
14
486
1
7
Order By: Relevance
“…It will also be noted that the four insulin-treated groups were less evidently heterogeneous than patients in the other analyses we have considered. Numbers were, however, relatively small, with 2,286 on insulin glargine alone, compared with 1,262 on NPH insulin, and once again a dosage-based comparison, as performed in the German study [23], did not prove feasible.…”
Section: First Observations In Manmentioning
confidence: 95%
See 4 more Smart Citations
“…It will also be noted that the four insulin-treated groups were less evidently heterogeneous than patients in the other analyses we have considered. Numbers were, however, relatively small, with 2,286 on insulin glargine alone, compared with 1,262 on NPH insulin, and once again a dosage-based comparison, as performed in the German study [23], did not prove feasible.…”
Section: First Observations In Manmentioning
confidence: 95%
“…Cancers take many years to develop, and it is therefore surprising that studies such as those reported in this issue of Diabetologia [10,[23][24][25] can claim to detect differences in cancer rates within a few years of exposure to different therapeutic agents. These observations, if confirmed, strongly suggest that the effects we are witnessing arise from differences in the rate of development of pre-existing malignant foci rather than malignant transformation and new cancer cell formation.…”
Section: The Insulin-igf-1 Axismentioning
confidence: 99%
See 3 more Smart Citations